A review of ONDC’s digital warfare in India taking on the e-commerce giants - Dash, Bibhu; Sharma, Pawankumar; F. Ansari, Meraj; Swayamsiddha, Swati (International Journal of Engineering and Technology, 2022)
Geographic and linguistic distances are becoming less relevant due to digital technology advances. Due to digitalization, E-commerce is one of the many technological breakthroughs that have directly and indirectly impacted consumers' lives. With the rise of e-commerce, consumers may more easily choose items that meet their interests, and quality and reputation can be verified. For this reason, e-commerce businesses have risen to prominence in consumers' lives. Customers may engage with sellers and buyers via online and mobile platforms for a unique selling or purchasing experience because the e-commerce industry relies on digital technologies. But with time, this market became opaque due to the monopolistic practices of some of the world's largest e-commerce companies, who began to exert influence over consumer purchasing habits. Those players' interests must be safeguarded in a country like India, where small retail firms control more than 80 percent of the retail segment. As a measure, the Indian government developed a new concept called Open Network for Digital Commerce (ONDC) to protect merchants and buyers. When it comes to online shopping, this ONDC architecture is going to have a significant impact. Without a doubt, ONDC is addressing numerous concerns regarding future Indian e-commerce challenges, even though it is unclear what ONDC aims to achieve with the network's many building pieces or what privacy and security protections it intends to put in place for data interchange. All the befits and challenges of ONDC are highlighted in this article.Â